The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/3634698
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Cosine Generalized Family of Distributions for Reliability Modeling: Characteristics and Applications with Simulation Study

Abstract: An extension of the cosine generalized family is presented in this paper by using the cosine trigonometric function and method of parameter induction concurrently. Prominent characteristics of the proposed family along with useful results are extracted. Moreover, two new subfamilies and several special models are also deduced. A four-parameter model called an Extended Cosine Weibull (ECW) with its mathematical properties is studied deeply. Graphical study reveals that the new model adopts right- and left-skewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…[16] discusses the TIIHLW distribution and its features. When the cause of the failure is known or unknown, the maximum likelihood method is applied; see [17,18]. TIIHLW (α, β, λ) has the cumulative distribution function…”
Section: Tiihlw Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] discusses the TIIHLW distribution and its features. When the cause of the failure is known or unknown, the maximum likelihood method is applied; see [17,18]. TIIHLW (α, β, λ) has the cumulative distribution function…”
Section: Tiihlw Distributionmentioning
confidence: 99%
“…Since Equations ( 17)-( 19) cannot be solved analytically, some numerical methods such as Newton's method must be employed to solve Equations ( 17), (18), and (19) and obtain estimates of the parameters α, β , and λ.…”
Section: Maximum Likelihood Estimationmentioning
confidence: 99%
“…The generalised Lindley distribution was first introduced in 2011 by Nadarajah et al, who showed that it outperforms gamma, log-normal, Weibull, and exponential distributions when taking bathtub hazard rate into account [12]. In 2021, Mahmood et al [19] published an enlarged Cosine generalised family of distributions for dependability modelling: characteristics and applications with simulation analysis, and Muse et al [20] suggested a new flexible form of the loglogistic distribution. Citations [5], [17], and [6] in 2022 explored a family of produced distributions with applications.…”
Section: Introductionmentioning
confidence: 99%
“…As a baseline hazard rate, many probability distributions for the number of competing causes of the event of interest have been offered. An interesting survey for the classical distributions and their survey can be referred to [30][31][32][33][34][35]. Table 1 shows the chronological review on the competing risk models under progressive censoring scheme with different baseline distributions.…”
Section: Introductionmentioning
confidence: 99%